ANALISIS NILAI TAMBAH DAN PENGOLAHAN ASAM GELUGUR (GARCINIA ATRIVIRIDIS GRIFF) KECAMATAN DOLOK PANRIBUAN KABUPATEN SIMALUNGUN PROVINSI SUMATERA UTARA - ASMINA HERAWATY SINAGA; MEI LINDA SIPAYUNG; TIURMAIDA NAINGGOLAN (LP2MTBM MAKARIOZ, 2021)
The purpose of this research is to know the process of processing the fruit of gelugur acid since the fruits are harvested, toknow the cost of processing the fruits of gelugur from the fruit is processed until ready to be marketed and to know the valueadded and the margin that occurs in the processing of the gelugur fruits. This study was conducted for approximately I monthwhere the research area is determined by purposive sampling in Kecamatan Dolok Panribuan, Kabupaten Simalungun. Thepopulation in this research is the entrepreneur who process the fruits of gelugur acid. The amount of processor of thisgelugur is 3 people using census method. The collected data was first tabulated based on the type and the need performedhypothesis testing in accordance with the hypothesis that has been formulated. The result showed that the process of theprocessing of gelugur acid fruit in the research area is still traditional. Using cutting tools there is no thought processor in thatdirection until the time this research is done, so the hypothesis stating that the process of processing fruits gelugur done inthe research area is still traditional, acceptable. The largest production cost of processing is the purchase of raw materials orfruit acid gelugur, which reached Rp. 37,059,889.82, so the hypothesis stating that the largest processing production costs inprocessing is the purchase of raw materials or fruit acid gelugur, can be accepted. Value added is abtained at 316.66%,which means greater than 50% and margin obtained by 166.43%, which means greater than 20%. Thus the hypothesiswhich states that the added value int the treatment of acid gelugur is >50% of the value of production costs, while theamount of margin is >20% the value of production costs, acceptable. This shows a real effect on the analysis of added valueand treatment of acid gelugur.